The Opportunities for Enhancing Psychosocial Support Strategies in Mataram, West Nusa Tenggara: Stakeholder-Driven Approaches - Mujahidin Hasanul Bisri; Ahmad Munjirin; Monita Oktaviawati; Norsuhaily Abu Bakar (Innovative: Journal Of Social Science Research, 2023)
Through stakeholder perspectives, this study aims to identify strategies that can enhance psychosocial support services in Mataram, West Nusa Tenggara. The research method employed was qualitative with purposive sampling techniques. Data collection was conducted through in-depth interviews, observation, and documentation, and descriptive data analysis was performed with Atlas—ti software. The research findings indicate that improving human resources' quality via capacity building, knowledge renewal, and expert involvement in training and program implementation is paramount. Furthermore, the scope of services must be broadened to include all age groups, such as adolescents, adults, and older people. Good cross-sector coordination is also crucial in increasing service responsiveness and monitoring patient progress. Educating families and communities is vital in reducing the stigma associated with mental disorders and increasing understanding. Innovative approaches, such as outdoor activities with a relaxed atmosphere, can be applied to public education to achieve better results. Additionally, community involvement in the evaluation process of psychosocial support programs must be increased to gain valuable feedback and ensure program relevance and sustainability. In conclusion, collaborative efforts involving human capital improvement, cross-sector coordination, community education, and stakeholder participation can significantly enhance the quality of psychosocial support services.